The Influence of Financial Knowledge, Financial Literacy, and Financial Technology on Financial Management Behavior Among Young Adults - Jennifer Jennifer; Sawidji Widoatmodjo (International Journal of Application on Economics and Business, 2023)
The purpose of this research is to analyze the effect of financial knowledge, financial literacy, and financial technology on financial management behavior of young adults in the city of Jakarta. The sample selection technique in this study was purposive sampling. The sample used in this study is 150 respondents, obtained through the distribution of online questionnaires. This research uses Smart PLS software version 3.2.9 to process the data. The result of the analysis shows that financial knowledge, financial literacy, and financial technology have a significant and positive effect on financial management behavior on young adults in the city of Jakarta.